Integrating Peer Learning Activities and Problem-Based Learning in Clinical Nursing Education - Suci Tuty Putri S.Kep., Ners., M.Kep; Sri Sumartini S.Kp., M.Kep (SAGE Publishing, 2021)
Introduction The implementation of nursing clinical learning in Indonesia has several challenges that require innovation in the learning method strategy. The method that has been used so far focuses on the hierarchical relationship between lecturers/preceptors and students, so that there are many shortcomings in learning outcomes. The application of the method of active learning with Peer Learning (PL) and Problem Based Learning (PBL) techniques has proven effective in classroom learning, but its rarely found in clinical learning. Objective The purpose of this study was to determine the effectiveness of the PL and PBL towards the achievement of clinical learning in nursing students. Methods The research method used a true experiment with a posttest only control group design, the sampling technique was taken by randomize control trial. An instrument for clinical learning achievement using AssCE. Results The analysis was carried out as descriptive and bivariate. The results showed the mean in the experimental group was 7.059 and the control group was 6.325. Further statistical test results were obtained p-value = 0.001 (p < 0.05) which showed that the average score there were differences in clinical learning achievement development scores. Conclusion Clinical learning using peer learning and PBL methods can directly improve various aspects of student competency achievement.